KOMUNIKASI PUBLIK SATGAS COVID TENTANG PROGRAM VAKSINASI COVID-19 KEPADA MASYARAKAT DI DESA PASAREAN KECAMATAN PAMIJAHAN - Nahrudin; Ernawati , Erna; Muslikhah, Febri Palupi (Fakultas Ilmu Dakwah dan Komunikasi, 2023)
This research is motivated by the attitude of the people who are still unsure about the Covid-19 vaccination. The Covid Task Force needs to take more effective communication strategy steps, thereby reducing the level of apathy and resulting in a change in attitude among the people who are still unsure about the Covid 19 vaccination. what happened between the Covid-19 Task Force and the community and factors influencing the success of public communication in Pasarean Village in receiving information about vaccines from the Covid task force with a low level of public trust. The research method used is a qualitative descriptive approach. The sample used in this research is people who have participated in the vaccination program in Pasarean Village. With data collection techniques by way of observation, interviews and documentation. The results of this study state that: public communication in Pasarean Village that occurs between the Covid -19 task force and the community consists of 2 face-to-face, namely by direct socialization and through the media (print media and social media) as well as the factor of receiving information in encourage the public to be able to know, like and want to take part in the activities held, one of which is with social media. The closeness of the communicator and the communicant is also one of the keys to the success of public communication as well as language style that is adjusted based on age and is able to have an effect on the community so that people are ready to do the vaccine.